The effect of sustainable marketing analysis on purchasing decisions with buying intention as a mediation: evidence from zero waste shop in Indonesia - Maulidah, Silvana; Ekawati, Aulia Dian; Faizal, Febriananda; Nasikh,; Sahro, Hanifatus; Shaleh, Mohammad Ilyas (Business: Theory and Practice, 2024)
The rapid social change in the world through global economic turmoil, social inequality, and degradation of the natural context triggered an increase in criticism of the marketing approach oriented towards the dimension of profit alone. The concept of modern marketing requires rebranding with sustainability issues, namely the sustainable marketing model. Marketers must present to consumers an active and responsible management attitude and openness and honesty in market communication. This study aims to investigate the influence of the application of sustainable marketing on purchasing decisions in zero waste shops, where purchase intention is a mediator. The dimensions of sustainable marketing include customer solution, customer cost, communication, and convenience. Quantitative research was undertaken by distributing survey questionnaires via google forms online. A total of 193 respondents were obtained from distributing questionnaires in Jakarta. The data was analyzed using Structural Equation Modelling-Partial Least Square (SEM-PLS). The analyses have proven that sustainable marketing positively affects purchase intention and purchase decisions. Purchase intention has a positive effect on purchase decision dan has functioned effectively as a mediator between sustainable marketing and purchase decision. This study contributes to a long-term-oriented marketing strategy by looking at the dynamics of healthy lifestyle changes that must be done quickly.